Open Inguinal Hernia Repair in Adults: An Update - Kumar H.R. (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
In this study, we look at the various types of open inguinal hernia repair that include tension-free and suture-based repairs. We also look at chronic pain after open inguinal hernia repairs. The open inguinal hernia repairs can be divided into tissue repair and mesh repair. Among the tissue repairs, the Shouldice repair is the most common repair that is performed, with the Bassini repair and Darning method being rarely performed. Mesh-based repairs are the most popular open inguinal hernia repair with the Lichtenstein repair the most common procedure that is performed. Several technical modifications have been done for the Lichtenstein repair which include using a larger mesh size, using interrupted sutures to anchor the mesh to the aponeurosis of the internal oblique muscle and greater overlap of the mesh over the pubic symphysis. The sutured-based repairs are not commonly performed with the Shouldice repair being the most performed, but the Desarda repair is slowly emerging as a viable sutured-based repair. We have conducted this review article to look at the current state of the various types of repairs for open inguinal hernia repair including their complications and recurrence rate. We also looked at the effect of chronic pain in open inguinal hernia repair. Open inguinal hernia repairs will continue to be one of the most common operations that are performed worldwide, and it will retain its place in the surgical treatment of inguinal hernias despite the introduction of laparoscopic inguinal hernia repair.